(untitled) (Journal of Engineering, 2024)
One of the primary functions of the DC motor is exemplified in its utilization for the automated operation of irrigation gates, which involves a variety of DC motor models. The DC motor chosen was influenced by the particular operational requirements of the irrigation gate. The ability to support the massive weight of the gate as well as the extreme pressure produced by river water currents are among these requirements. The gate motor utilized functions at a sluggish pace of 20 revolutions per minute. The approach employed involves tuning utilizing the Ziegler-Nichols (ZN) method. The (Proportional-Integral-Derivative) PID controller is designed to precisely manage a DC motor’s position, improving the motor’s overall performance. The parameters were designed to be Kp = 17, Ti = 1, and Td = 0.1. The Simulation derived from the analysis of MATLAB step response data are side by side with algorithm utilized to certain the dynamic response of the closed-loop configuration. Essential Specifications such as rise time and settling time, both measured in seconds, will be integrated into the simulation outcomes. The utilization of the (ZN) based algorithm for adjusting the gain constants of the PID control system tends to yield superior outcomes in comparison to that under a unity feedback control system .The rising time was 12.6, but when performance improved, it dropped to 0.713. This improvement is also applicable to the settling time, which decreased from 22.4 to 1.13. The holistic evaluation demonstrates that the (ZN) method yields superior performance in contrast to a system employing unity feedback control.